IMPLEMENTATION OF THE SOCIALIZATION OF BASIC AGRARIAN LAW IN THE LAND REGISTRATION PROCESS AT THE VILLAGE LEVEL - Rahmawati, Rahmawati; Afiyah, Siti; Bagus, Salahudin Serba; Sundari, Ariefah (EQUALEGUM International Law Journal, 2025)
Background. The issue of agrarian reform in Indonesia has long been a central theme in the country’s legal, political, and social development. This study aims to analyze the implementation of the amended Basic Agrarian Law in the land registration process at the village level, particularly in Ngarum Village, Lamongan, and to evaluate the effectiveness of socialization programs in improving community legal awareness regarding land registration. Research method. Employing a qualitative socio-legal approach, the research explores how legal norms interact with local institutions and community practices. Data were collected through interviews, observations, and legal document analysis. Findings. The implementation of land registration under Law Number 14 of 2024 still encounters obstacles such as limited community legal awareness, weak village administrative capacity, and the lack of data integration with land agencies. Nevertheless, supporting factors such as improved public interest in land certification and the strategic role of village leaders have been identified. The evaluation of socialization activities indicates a significant increase in awareness levels, although this improvement does not always translate into actual registration practices due to structural and cultural barriers. The analysis highlights a gap between the legal framework and its implementation, emphasizing the need for strengthening institutional capacity and enhancing community legal education. Conclusion. Successful implementation requires multidimensional strategies that involve legal, institutional, cultural, and technological support tailored to rural contexts.